Clinical Efficiency of Non-invasive Prenatal Screening for Common Trisomies in Low-Risk and Twin Pregnancies - Xu, Yanfei; Jin, Pengzhen; Lei, Yu; Qian, Yeqing; Xu, Yuqing; Wang, Miaomiao; Jin, Jinglei; Yin, Yixuan; Dong, Minyue (Frontiers in Genetics, 2021)
To evaluate the clinical efficiency of non-invasive prenatal screening (NIPS) for fetal aneuploidies in low-risk and twin pregnancies, patients who received NIPS in a tertiary university hospital were enrolled, and their clinical data, NIPS results and pregnancy outcomes were collected. Patients were divided into singleton and twin pregnancies, and then those with singleton pregnancies were divided into low- and high-risk pregnancies. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were estimated. Comparisons were made on the clinical efficiency of NIPS between singleton and twin pregnancies, as well as between low- and high-risk pregnancies. Of 66,172 patients enrolled, 59,962 were eligible for analysis. The sensitivity, specificity and NPV were ≥ 99% in singleton and twin pregnancies. The PPVs were 90.4, 56.6, and 13.0% in singleton pregnancies, while 100, 33.3, and 0% in twin pregnancies for trisomy 21 (T21), trisomy 18 (T18) and trisomy 13 (T13), respectively (P > 0.05 for all). The PPVs were 97.4 and 90.0% in high-risk pregnancies, while 78.6 and 16.7% in low-risk pregnancies for T21 and T18, respectively (P < 0.05 for all). In summary, the performance of NIPS in singleton pregnancies was similar to that in twin pregnancies. NIPS can be recommended for all pregnancies regardless of the risks.